Concentraciones séricas de la tiroxina (T4) y de la triyodotironina (T3) en sujetos sanos y en pacientes con disfunción tiroidea - Pajuelo E. , Alfonso (1979)
These are the results obtained by measuring the serum concentration of total thyroxine, T4, using a competitive protein binding (CPB) technic and triiodothyronine, T3 (3, 3,5 triiodo-l-thyronine), with a radioinmunoassay technic employing Sephadex columns to separate the thyronines.  We measured the serum thyroxine in 61 normal subjects obtaining an average of 7.4 +- 1.9 (1 SD) ug/100 ml of serum (range 4.1 - 11 ug/100 ml); a group of 16 clinical hyperthyroid patients had an average of T4 of 19.8 +- 6.8 (1SD) ug/100 ml (range 12-39 ug/100 ml) and 11 hypothyroid patients had an average of 2.4 +- 1.4 (1 SD) ug/100 ml of serum (range 0.2-4 ug/100 ml). The serum concentration of triiodothyronine (T3) performed in 52 normal subjects was 157 +- 31 (1 SD) ng/100 ml of serum (range 110-225 ng/100 ml). In 14 hyperthyroid patients the average was 572 +- 349 (1SD) ng/100 ml (range 275-1360 ng/100 ml) and in 9 hypothyroid patients the average was 60 +- 21 (1 SD) ng/100 ml of serum (range 35-85-ng/100 ml). A case is reported with the clinical characteristics of a toxic nodular goiter in which initially we found only increased amount of serum triiodothyronine and no in other parameters of thyroid function. We think that this could be a case of T3 thyrotoxicosis, perhaps transitory to the more common type of hyperthyroidism.  The measurement of these hormones has given us a more precise understanding of the functional thyroid status of the patients in out hospital.